2012
DOI: 10.1074/jbc.m112.394924
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmunoendocrine Regulation of the Prion Protein in Neutrophils

Abstract: Background: Prion protein (PrP C ) modulates inflammation, and prion diseases affect neutrophil numbers and functions, but the regulation of PrP C in neutrophils is unknown. Results: Inflammation and stress massively up-regulated PrP C in neutrophils via glucocorticoids and TGF-␤. Conclusion:We show a novel pathway of regulation of PrP C , with functional consequences for neutrophils. Significance: Systemic control of the expression and function of PrP C broadly modulates cellular physiology and pathology.The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 63 publications
2
23
0
Order By: Relevance
“…The CD47-Sirpa signaling system, however, also regulates properties of polymorphonuclear cells, such as adhesion, migration and phagocytosis, as well as macrophage-mediated clearance of apoptotic neutrophils, with robust functional consequences (Parkos et al, 1996;Liu et al, 2001;Lawrence et al, 2009;Myers et al, 2011;Zen et al, 2013;Stenberg et al, 2013Stenberg et al, , 2014Greenlee-Wacker et al, 2014). Interestingly, we have found no difference between Prnp-null and wild type neutrophils taken from B10.129Ola mice in their sensitivity to spontaneous or peroxideinduced apoptosis in vitro (Mariante et al, 2012), nor in their recruitment to the peritoneal cavity following in vivo injections of zymosan (R.M. Mariante et al, unpublished results).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The CD47-Sirpa signaling system, however, also regulates properties of polymorphonuclear cells, such as adhesion, migration and phagocytosis, as well as macrophage-mediated clearance of apoptotic neutrophils, with robust functional consequences (Parkos et al, 1996;Liu et al, 2001;Lawrence et al, 2009;Myers et al, 2011;Zen et al, 2013;Stenberg et al, 2013Stenberg et al, , 2014Greenlee-Wacker et al, 2014). Interestingly, we have found no difference between Prnp-null and wild type neutrophils taken from B10.129Ola mice in their sensitivity to spontaneous or peroxideinduced apoptosis in vitro (Mariante et al, 2012), nor in their recruitment to the peritoneal cavity following in vivo injections of zymosan (R.M. Mariante et al, unpublished results).…”
Section: Discussionmentioning
confidence: 61%
“…Among the immune cells, PrP C has been implicated in the physiology of lymphocytes, macrophages, dendritic cells, neutrophils and others (Isaacs et al, 2006;Mariante et al, 2012), and a role of PrP C was reported in the activation of microglia (Brown et al, 1998). The latter are mononuclear phagocytes resident in the brain parenchyma, and constitute about 5 to 20% of the total number of glial cells, depending on the specific region of the brain (Lawson et al, 1990;Perry and Gordon, 1991).…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, the scaffold hypothesis is consistent with the often controversial functional properties assigned to the prion protein, which extend far beyond the nervous system, including immune responses (11,12), cancer biology (6,13), heart oxidative stress (14), glucose homeostasis (15), and stem cell regulation (16,17). Such widespread influence probably depends on the ability of PrP C to bind several partners, varied combinations of which populate the cell surface of distinct cell types (5,10).…”
mentioning
confidence: 64%
“…Similarly, systemic LPS upregulated PrP C in circulating neutrophils [60], whereas LPS incubation increased PRNP expression in neuronal cell cultures [61]. As expected, PRNP expression was low in PrP C -deficient goats, regardless of treatment, which probably reflects nonsense-mediated mRNA decay [62].…”
Section: Discussionmentioning
confidence: 95%